Economic and Noneconomic Determinants on Indian Inbound Tourism - Tyagi, Nanita (Anais Brasileiros de Estudos Turísticos, 2022)
This study was intended to study and analyze the impact of economic and non-economic determinants on Indian inbound tourism using time series data from 2011 to 2020. The data was collected encompassing 20 top FTA receiving countries to India. The study focuses on 18 possible determinants instrumental in Indian Inbound tourism. Initially, these 18 determinants were identified on the basis of opinion propounded by experts from industry and academia. Then the content analysis was done from 126 empirical research papers to arrive at its inclusion. Having explored these determinants for Indian Inbound tourism, an analysis was done by pooled and fixed-effects models of multiple regression. A Country-wise data set was used to found country-specific determinants of foreign tourists' arrival to India. The results shows that the Consumer Price Index (CPI), Gross Domestic Products (GDP), Purchasing Power Parity (PPP) are economic determinants having a positive impact on the Number of Foreign Tourist Arrivals while Climate, Culture, Common Language and Religion as noneconomic determinants which also have positive impact on the dependent variable and are statistically significant whereas, the factors like Bilateral Trade, Exchange rate, Relative price, and Safety and Security at destination sites have found no statistically significant impact on Indian inbound tourism.